PENGEMBANGAN BAHAN AJAR MATERI BILANGAN BERBASIS SAINTIFIK UNTUK ANAK USIA 5-6 TAHUN DI TK ISLAM ALKAUTSAR INDRALAYA - Issaura Dwi selvi (Tumbuh Kembang: Kajian Teori dan Pembelajaran PAUD, 2019)
This development research aims to produce teaching materials in the form of handouts for teachers in Al-Kautsar Indralaya Islamic Kindergarten. Development is done by using ADDIE model (analysis, design,development, implementation and evaluation). The evaluation was done by Tessmer's formativeevaluation with four evaluation phases, namely self evaluation, expert review, one-to-one evaluation andsmall group evaluation. Data collection techniques use observation and walkthrough. Experimental resultsHandout 1 of 3.75, Handout 2 of 3.75, Handout 3 of 3.80, Handout 4 of 3.65, Handout 5 of 3.75 andHandout 6 of 3.80 (with very valid category) . Furthermore, the one to one evaluation stage obtained theaverage of teacher observation with Handout 1 of 87%, Handout 2 of 88%, Handout 3 of 87%, Handout 4of 90%, Handout 5 of 87% and Handout 6 of 88% with excellent category). While in the small groupevaluation, the average observation result on Handout 1 of 90%, Handout 2 of 90%, Handout 3 of 92%,Handout 4 is 90%, Handout 5 of 88%, and Handout 6 of 90% (with excellent category). Therefore, it canbe concluded that the teaching materials of scientifically based number of numbers is valid and practicalfor use by the teacher.